PENGARUH SUPERVISI AKADEMIK DAN MOTIVASI KERJA GURU TERHADAP MUTU PEMBELAJARAN PADA MADRASAH TSANAWIYAH SWASTA DI KECAMATAN TAHUNAN KABUPATEN JEPARA - Jamal Abdul Naser; Ngasbun Egar; Ghufron Abdullah (STKIP Subang, 2023)
The quality of learning in madrasahs is influenced by many factors, including academic supervision and teacher work motivation. In managing madrasahs, academic supervision greatly influences the quality of learning. This heavy responsibility requires cooperation with the staff as well as comprehensive support from the community or stakeholders. Teacher supervision and work motivation play an important role in improving the quality of learning. In other words, academic supervision helps create progress or quality of learning. The aims of this research are: (1) To explain the influence of academic supervision on the quality of learning at private Tsanawiyah Madrasahs in Tahunan District, Jepara Regency, (2) To explain the influence of teacher work motivation on the quality of learning at private Tsanawiyah Madrasahs in Tahunan District, Jepara Regency, (3) ) To explain the influence of academic supervision and teacher work motivation on the quality of learning at private Tsanawiyah Madrasahs in Tahunan District, Jepara Regency. This research approach is quantitative research. The population in this study was 147 teachers from 7 private Madrasah Tsanawiyah (MTs) in Tahunan District, Jepara Regency. A sample of 107 teachers was selected using proportional random sampling technique at each madrasah. Data collection uses questionnaires. Data processing and descriptive data analysis, using the SPSS for Windows version 20. The research findings show: (1) there is an influence of academic supervision on the quality of learning of 40.4% with the implementation of supervision as the weakest factor, (2) there is an influence of teacher work motivation on the quality of learning of 23.5% with external motivation as the weakest factor, (3) there is an influence of academic supervision and teacher work motivation together on the quality of learning of 41.4% with the implementation of learning as the weakest factor. Suggestions to (1) madrasah heads to intensify evaluation of academic supervision results and report periodically each semester for all teachers, (2) madrasah heads to increase teacher work motivation by giving awards/rewards to teachers for his achievements, (3) teachers to play a role in madrasah strategic agendas.